ATR and MKP1 play distinct roles in response to UV‐B stress in Arabidopsis. (20th February 2013) - González Besteiro, Marina A.; Ulm, Roman
Summary Ultraviolet‐B (UV‐B) stress activates MAP kinases (MAPKs) MPK3 and MPK6 in Arabidopsis. MAPK activity must be tightly controlled in order to ensure an appropriate cellular outcome. MAPK phosphatases (MKPs) effectively control MAPKs by dephosphorylation of phosphothreonine and phosphotyrosine in their activation loops. Arabidopsis MKP1 is an important regulator of MPK3 and MPK6, and mkp1 knockout mutants are hypersensitive to UV‐B stress, which is associated with reduced inactivation of MPK3 and MPK6. Here, we demonstrate that MPK3 and MPK6 are hyperactivated in response to UV‐B in plants that are deficient in photorepair, suggesting that UV‐damaged DNA is a trigger of MAPK signaling. This is not due to a block in replication, as, in contrast to atr, the mkp1 mutant is not hypersensitive to the replication‐inhibiting drug hydroxyurea, hydroxyurea does not activate MPK3 and MPK6, and atr is not impaired in MPK3 and MPK6 activation in response to UV‐B. We further show that mkp1 leaves and roots are UV‐B hypersensitive, whereas atr is mainly affected at the root level. Tolerance to UV‐B stress has been previously associated with stem cell removal and CYCB1;1 accumulation. Although UV‐B‐induced stem cell death and CYCB1;1 expression are not altered in mkp1 roots, CYCB1;1 expression is reduced in mkp1 leaves. We conclude that the MKP1 and ATR pathways operate in parallel, with primary roles for ATR in roots and MKP1 in leaves.